2020
DOI: 10.4049/jimmunol.204.supp.249.4
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modification enables viral RNA to escape recognition by RNA sensor RIG-I

Abstract: Internal N6-methyladenosine (m6A) modification of RNA is one of the most abundant modifications in eukaryotic cells as well as in viruses. However, the biological role(s) of RNA m6A in virus-host interaction remains elusive. Using human metapneumovirus (hMPV), a medically important non-segmented negative-sense RNA virus as a model, we demonstrate that m6A serves as a molecular marker for innate immune discrimination of self from nonself RNAs. We show that hMPV RNAs are m6A methylated and that viral m6A methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The study also reported that the SARS-CoV-2 genome contains m 6 A modifications enriched in the 3' region of RNA and that RIG-I binds to SARS-CoV-2 viral RNAs and is inhibited by m 6 A RNA modifications [30]. In patients with severe coronavirus disease 2019 (COVID-19), METTL3 is reduced and inflammatory genes are induced [30], which agrees with the findings in other viruses [29]. It has been shown that host m 6 A components interact with viral proteins to modulate SARS-CoV-2 replication [31].…”
Section: Cellular Response To Rna Methylationsupporting
confidence: 83%
See 2 more Smart Citations
“…The study also reported that the SARS-CoV-2 genome contains m 6 A modifications enriched in the 3' region of RNA and that RIG-I binds to SARS-CoV-2 viral RNAs and is inhibited by m 6 A RNA modifications [30]. In patients with severe coronavirus disease 2019 (COVID-19), METTL3 is reduced and inflammatory genes are induced [30], which agrees with the findings in other viruses [29]. It has been shown that host m 6 A components interact with viral proteins to modulate SARS-CoV-2 replication [31].…”
Section: Cellular Response To Rna Methylationsupporting
confidence: 83%
“…Importantly, research on RNA modification has revealed that viruses acquire m 6 A in their RNA as a means of mimicking cellular RNA to avoid detection by innate immunity. This finding implies that the m 6 A modification enables viral RNA to evade RNA sensor RIG-I [29]. A study has suggested that viral m 6 A RNA modification can be used as a vaccine target to attenuate viral infections, such as those caused by human metapneumovirus [29].…”
Section: Cellular Response To Rna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Given the role of 2′-O-methylation and m 6 A in marking RNA as self, targeting these modifications may serve as potential strategy to enhance mRNA vaccine efficacy. 45,46 Inflammasomes are large protein platforms triggered by various internal or external stimuli via NLR members, to promote caspase-1-dependent cleavage and maturation of inflammatory cytokines IL-1β and IL-18, as well as to induce gasdermin D-induced pyroptotic cell death. 47 Overactivation of inflammasome is closely related to a variety of inflammatory and autoimmune diseases, such as diabetes, 48 Alzheimer's disease 49 and atherosclerosis.…”
Section: Rbps Regulate Innate Immune Sensing In Autoimmunity and Auto...mentioning
confidence: 99%